Integrated Disease Control of Rice Blast - Yulianto Yulianto (Iptek Tanaman Pangan, 2017)
Blast disease caused by Pyricularia oryzae Cav. fungus, is infecting rice crop in dry lands, and also in the rainfed and irrigated lands. Yield losses due to blast depending on the intensity of the disease. At a high degree of the disease intensity, yield loss reaches up to 90%. Symptoms of the disease often appear on rice leaf (leaf blast) or in the panicle neck (neck blast). Panicle neck blast is more detrimental than leaf blast disease. The fungus has many races which are easily adapting to the environmental conditions. The new races are formed by genetic recombination and by mutation, where the new races usually are more virulence than the old ones. Genetic resistance on a rice variety my be broken, depending on the environmental conditions or planting times. In the highland the disease is very rare and often at low disease intensity. Conversely, blast disease is more prevalence in the lowlands and often with high disease intensity. Blast pathogen survives on weeds and on rice straw which functions as a source of inoculum. Blast disease control using a single component will not be effective, and therefore an integrated control management by applying multiple components is suggested, including: sanitation, removing the diseased plants and weeds acting as alternate host, planting resistant varieties, avoid an excessive use of N fertilizer, less crowded plant spacing, proper irrigation management, varietal rotation, and precise use of fungicide, if ever needed.